2000
DOI: 10.1046/j.1442-9071.2000.00237.x
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects of topical antiglaucoma drugs on the ocular surface

Abstract: The conclusion was that it is possible that conjunctival surface and tear film function change after the long-term use of antiglaucoma medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
67
1
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(78 citation statements)
references
References 17 publications
2
67
1
3
Order By: Relevance
“…First, corneal and conjunctival fluorescein staining was not evaluated, although this has been extensively studied in the past. 25,35,39,[46][47][48] Second, our study did not consider the possibility that glaucoma patients' (in the medicated and posttrabeculectomy groups) tear function may be due to dry eye that was independent of their glaucoma treatment. Glaucoma patients on concomitant systemic (eg, hormonal pills) 49 or ocular medications (eg, artificial tear lubricants), 50 which can affect dry eye test parameters, were also not considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, corneal and conjunctival fluorescein staining was not evaluated, although this has been extensively studied in the past. 25,35,39,[46][47][48] Second, our study did not consider the possibility that glaucoma patients' (in the medicated and posttrabeculectomy groups) tear function may be due to dry eye that was independent of their glaucoma treatment. Glaucoma patients on concomitant systemic (eg, hormonal pills) 49 or ocular medications (eg, artificial tear lubricants), 50 which can affect dry eye test parameters, were also not considered.…”
Section: Discussionmentioning
confidence: 99%
“…The far majority of studies only reported symptoms 24 or the tear function tests with preset thresholds. 22,25,26 Another study reported that only 4.8% and 33.8% of patients on anti-glaucoma medications had TBUT and Schirmer's test values of 410 s and 410 mm, respectively, as compared with a healthy population of 100% above these thresholds. 27 We hypothesize that TFO may be raised in glaucoma patients, both on topical therapy and post trabeculectomy, compared with normal controls.…”
Section: Introductionmentioning
confidence: 99%
“…Topical hypotensive therapy with fixed combinations (prostaglandin analog and beta blocker eye drops) has been observed to increase the expression of the inflammatory markers HLA-DR and interleukin-6 with resultant deterioration in the ocular surface after three months of therapy. 27,28 The anti-inflammatory effect of topical cyclosporine 0.05% administered twice daily has been proven to be beneficial to reduce the inflammatory effects of mild to moderate dry eye disease. 15,20 Our study evaluated the concurrent effect of topical cyclosporine 0.05% therapy on the ocular surface in patients of long-term ocular hypotensives.…”
Section: Discussionmentioning
confidence: 99%
“…We used IVCM because this technique is minimally invasive, and it is effective in evaluating the histopathology of surface disease (Mastropasqua et al 2006;Messmer et al 2006;Hong et al 2010;Le et al 2010;Wakamatsu et al 2010;Zhu et al 2010) and the toxic effects of glaucoma therapy (Arici et al 2000;Messmer et al 2006;Ciancaglini et al 2008;Martone et al 2009;Bergonzi et al 2010). Our study showed that no changes occurred throughout followup in both controls and patients treated with preservative-free timolol; on the opposite, BAK-preserved eye drops were associated with signs of ocular surface inflammation (lower goblet cell density and epithelial irregularity) after 12 months of treatment.…”
Section: Discussionmentioning
confidence: 99%